The nematicidal potential of Moringa oleifera extracts and rhizobacteria against Meloidogyne incognita in tomato - Azeem, Wajahat; Mukhtar, Tariq; Inam-ul-Haq, Muhammad; Khan, Muhammad Azam; Ibrahim, Muhammad Suhail; Hassan, Ahmad; Regmi, Homan; Duncan, Larry W. (Frontiers in Plant Science, 2025)
Here we report the effects of aqueous extracts of the plant Moringa oleifera and rhizobacterial strains, Bacillus australimaris (BA-LWD73) and B. thuringiensis (BT-WAG41), applied singly and in combination, on tomato growth and Meloidogyne incognita infection. Plant height, root length, shoot and root biomass (fresh and dry), were significantly increased by most treatments compared to the control. The combined treatment of BA-LWD73 + M. oleifera produced the highest plant height (96.94 cm) and root length (30.48 cm). The highest shoot biomass was observed in BA-LWD73 alone treatment while root biomass was generally lower in all treatments than in the control. M. incognita induced, root gall rating, number of eggs per root system, second stage juveniles (J2), and reproduction rate, were significantly reduced in treatments involving M. oleifera and BA-LWD73, either alone or in combination. The lowest root gall rating (2.67) and J2 count (680) were observed in B. australimaris LWD73 + M. oleifera treatment. FTIR analysis of M. oleifera extract indicated the presence of functional groups such as hydroxyl, C=C, S=O, and C–O, suggesting bioactive potential. GC-MS analysis revealed six phytocompounds, with 5-Hydroxymethylfurfural (71.76%) as the dominant component, all known for antimicrobial and nematicidal activities. Moreover, volatile organic compounds from BA-LWD73 included 1H-Indole (87.46%) and 2-Nonanone (6.54%), known for their nematicidal properties. These findings highlight the potential of rhizobacteria and plant extracts in promoting tomato growth and suppressing M. incognita infection.